Islamic commercial law - Saleem, Muhammad Yusuf (John Wiley & Sons, 2013)
Filling a gap in the current literature, Islamic Commercial Law is the only book available that combines the theory and practice of Islamic commercial law in an English-language text. From the experts at the International Islamic University Malaysia, the book examines the source materials in the Qur'an and Hadith, and highlights the views and positions of leading schools of Islamic law, without burying the reader in juristic minutia. It combines theory with practice to address the needs of students while providing a pragmatic treatment of Islamic contracts. It provides diagrams for individual contracts to reveal the type and nature of the contractual relationships between parties and discusses all types of fundamental transactions, including sales, loans, debt transfers, partnerships, and more.